1989
DOI: 10.1093/jnci/81.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Is Alcohol Consumption Related to Breast Cancer? Results From the Framingham Heart Study

Abstract: We studied the relation between alcohol consumption and breast cancer among women in the Framingham Heart Study cohort. A total of 2,636 women aged 31-64 years provided information on alcohol consumption at the second biennial examination. They were followed for up to 32 years; during this period, breast cancer was diagnosed in 143 of these women. Alcohol intake was also assessed at 10 and 20 years of follow-up and every 2 years thereafter. In analyses using only baseline alcohol intake, the multiple risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
2
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 0 publications
0
14
2
1
Order By: Relevance
“…Results showed marked inconsistencies, because of difficulties in measuring and quantifying its consumption (1,2). Unlike other papers (21)(22)(23)(24), this hospital-based case-control analysis showed a protective effect of alcohol against breast cancer, independent of age, reproductive factors, lactation, and even smoking. Compared to Western women, female drinkers are not as common among Orientals, least of all heavy drinkers.…”
Section: Discussioncontrasting
confidence: 81%
“…Results showed marked inconsistencies, because of difficulties in measuring and quantifying its consumption (1,2). Unlike other papers (21)(22)(23)(24), this hospital-based case-control analysis showed a protective effect of alcohol against breast cancer, independent of age, reproductive factors, lactation, and even smoking. Compared to Western women, female drinkers are not as common among Orientals, least of all heavy drinkers.…”
Section: Discussioncontrasting
confidence: 81%
“…Most studies have found no clear association 3,8,13,27,33,[36][37][38]40) while some investigators have suggested an unfavorable effect of smoking habits on breast cancer 1, 35,39) In the present study, smoking habits were found to be associated with breast cancer risk, likewise a previous study conducted in Nagoya, Japan 35) In our study, we failed to detect clear dose-response relationship between the number of cigarettes smoked per day and breast cancer risk. Nevertheless, more detailed studies will be warranted on smoking habits, since our findings certainly indicate a positive association of smoking habits with breast cancer risk in females in Japan.…”
Section: Resultscontrasting
confidence: 75%
“…A positive association between alcohol consumption and breast cancer has been reported in many3, 5,6,8,11,15,21.22.34) but not all7, 10,13,27,32,33,35) epidemiological studies. The present study, however, did not show a significantly larger RR for current drinkers.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Most reliable evidence on the subject is available from large cohort studies with detailed smoking histories obtained before the occurrence of the disease. Studies such as the nurses' health study and the Framingham heart study have failed to show any association between cigarette smoking and breast cancer 2 3. Furthermore, a reduction in the risk of breast cancer among smokers has been reported in cohort studies as frequently as an increase 4.…”
mentioning
confidence: 99%